The Correlation between Family ClimatewithStudents Emotional Intelligenceof XI IPA SMAN in Parepare - St. Humaerah Syarif (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Negeri Makassar, 2017)
The study aimed at examining (1) describe family climate and students emotional intelligenceof XI IPA SMAN in Parepare, (2) correlation between family climate and students emotional intelligenceof XI IPA SMAN in Parepare. The kind of the study was ex-post facto research. The population of the study was the entire students of grade XI IPA at SMAN in Parepare. Data were collected with 230 samples taken by employing proportional random sampling technique. Data were analyzed by employing statistics descriptive and inferential analysis. The result of the study revealed that (1) the family climate of grade XI IPA students at SMAN in Parepare was in condusive category and emotional intelligence was in fair category, (2) there was correlation between family climate and emotional intelligence, and (3) the contribution of family climate toward emotional intelligence was 1,51%.